Improved Learning Outcomes of Natural Science Lesson Grade V Assisted Cooperative Learnng Models - Faiqoh Faiqoh (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in science grade V elementary schools with cooperative learning model The research conducted was a Classroom Action Research (PTK) with three cycle, with each cycle consisting of one meeting. The stages of each  cycle are planning, implementing, observing and reflecting. In the first cycle the student who completed were 45%. In the second cycle students who completed were 70%. In the third cycle students who completed were 95%. There result indicate that the cooperative learning model can improve student learning outcomes, especially grade V science on human circulatory System highlights at SD Negeri Kreman 01.